2007
DOI: 10.1074/jbc.m701096200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Dissection of Ca2+-binding Sites in the Extracellular Domain of Ca2+-sensing Receptor

Abstract: [Ca 2ϩ ] o ) the receptor and that cause familial hypocalciuric hypercalcemia and neonatal severe hyperparathyroidism (in the former) and autosomal dominant hypoparathyroidism (in the latter case) (20, 21).The CaSR and other members of family C of the G proteincoupled receptor consist of a large extracellular domain (ECD), a transmembrane domain with seven transmembrane segments, and an intracellular C-tail segment (22,23). Based on the functional responses at the cellular level, the ECD regions have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 64 publications
(66 reference statements)
5
109
2
Order By: Relevance
“…3 and 4). Such population studies were also reported in our previous studies (25,26). Results from Western blot and immunofluorescence staining using an anti-CaSR antibody indicated essentially equivalent expression of WT CaSR as well as its variants on the cell surface (Fig.…”
Section: Table 1 Analysis Of Correlated Motions Of Wt Casr Model Strusupporting
confidence: 53%
See 4 more Smart Citations
“…3 and 4). Such population studies were also reported in our previous studies (25,26). Results from Western blot and immunofluorescence staining using an anti-CaSR antibody indicated essentially equivalent expression of WT CaSR as well as its variants on the cell surface (Fig.…”
Section: Table 1 Analysis Of Correlated Motions Of Wt Casr Model Strusupporting
confidence: 53%
“…By using our own computational algorithms, we previously identified five putative Ca 2ϩ -binding sites in the modeled CaSR ECD (Fig. 1) (25,26,45). Among these, site 1 is located in the hinge region between the two lobes in the Venus flytrap motif.…”
Section: Molecular Connectivity Among Predicted Calcium-binding Sitesmentioning
confidence: 99%
See 3 more Smart Citations